Peningkatan Bantuan Keuangan APBD Kabupaten/Kota Dalam Mendukung Kinerja Pemerintah Kota Surabaya Di Provinsi Jawa Timur - Suyanto (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2022)
Basically economic development is an effort to increase capacity and freedom of choice. The creation of economic development is very dependent on the role of the government which is reflected in government spending. The ability of local governments to manage finances as outlined in the "APBD" directly or indirectly reflects the ability of regions to provide funds for the implementation of governmental tasks, development, and community social services. One of the tools for analyzing the performance of local governments in managing their regional finances is to analyze the financial ratios for the APBD that have been set and implemented. According to the provisions of the Regional Autonomy Law, regional authorities have the responsibility to provide various services to the community based on the principles of transparency, participation and responsibility. This study intends to determine the extent of effectiveness and efficiency in realizing local revenues Keyword: Effectiveness, Efficiency, Regional Finance